2018
DOI: 10.48550/arxiv.1804.09645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global existence and decay to equilibrium for some crystal surface models

Abstract: In this paper we study the large time behavior of the solutions to the following nonlinear fourthorder equationsThese two PDE were proposed as models of the evolution of crystal surfaces by J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The proof of this Theorem follows the approach in [18]. We define the new variable vpx, tq " upx, tq ´xu 0 y.…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…The proof of this Theorem follows the approach in [18]. We define the new variable vpx, tq " upx, tq ´xu 0 y.…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…This equation has been derived in [8], and again more recently in [10], as a model in epitaxial growth of thin films. Two recent works have analyzed this model; Granero-Bellinchon and Magliocca have proved global existence of small solutions on the torus, and decay to equilibrium [6]. On free space rather than the torus, Liu and Strain have demonstrated global existence of small solutions, decay to equilibrium, and analyticity of solutions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in multiple space dimensions, none of the above conditions can really be expected. More recently, the authors in [10] introduced the change of variable 3 The equation was then coupled with the initial and periodic boundary conditions. The existence of a "much stronger" weak solution than the one in [14] was obtained, provided that the initial data was suitably small,.…”
Section: Introductionmentioning
confidence: 99%
“…To mention a few, we refer the reader to [7,13,14] for solutions that contain measures. The study of exponential decay of solutions can be found in [10,12]. Development of singularity and finite extinction of solutions were considered in [8].…”
Section: Introductionmentioning
confidence: 99%